Automatic Consumption Management for Prepaid Electricity Meter with NILM - Souza, W.; Garcia, F. [UNESP]; Moreira, A.; Marafao, F. [UNESP]; Silva, L. (Ieee-inst Electrical Electronics Engineers Inc, 2020)
Recently, the Brazilian Electricity Regulatory Agency (ANEEL) regularized the electricity prepayment system and opened a general discussion about the technologies, resources, and implementations for the prepayment metering system. In several countries, the consumer charges the value equivalent to the kilowatt-hours that he wishes to buy for use. However, some consumers purchase credit with the expectation that the charge remains for a specific time, but they may be surprised with the credit end before the expected time. For this reason, this paper proposes automatic consumption management for prepaid meters that analyzes the consumer appliance behavior, performs the temporal analysis of consumption by appliances, defines the cost management per load with high energy consumption and sends sound signals to the consumer ends the appliance usage. The objective of this management system is to ensure that the credit will be used for the consumer expected time.
Keywords: Meters; IEEE transactions; Energy consumption; Indexes; Context modeling; Monitoring; Smart meters; Cognitive meter; Electric consumption management; Prepaid electric meter; Smart metering system